Peningkatan Ketahanan Mental Pelaku UMKM Agroforestry “Goatzilla” melalui Program Konseling Psikologis Ringan - Muhamad; Chantika Imarah Khairunnisa; Netti Ermawati (Direktorat Pengabdian kepada Masyarakat, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play an important role in strengthening local economies and supporting community welfare. In Kandangtepus Village, Senduro District, Lumajang Regency, East Java, most community members depend on agroforestry systems that integrate farming, livestock, and agricultural product processing activities. Despite their economic potential, MSME actors in this area often face various challenges, including market uncertainty, workload pressure, and limited institutional support, which may affect their psychological well-being and business sustainability. These conditions formed the basis for selecting the location and implementing psychological support activities. This study aimed to describe the implementation of a light psychological counseling program and identify its potential contribution to strengthening entrepreneurial motivation and resilience among agroforestry-based MSME actors at “Goatzilla.” A descriptive qualitative approach was employed, with data collected through semi-structured interviews, participatory observations, and reflective discussions with MSME owners. The findings indicated that MSME actors experienced several psychological challenges related to work demands and business sustainability concerns. The counseling sessions provided opportunities for self-reflection and facilitated discussions regarding personal strengths, obstacles, and adaptive coping strategies. Participants demonstrated positive responses toward the intervention, particularly in recognizing personal resources and developing more adaptive perspectives regarding business challenges. From the perspective of motivational and resilience theories, light psychological counseling can serve as a supportive approach to enhancing psychological capacity and sustaining entrepreneurial persistence. Therefore, integrating psychological support into community empowerment programs may strengthen MSME resilience and contribute to long-term community development.